Innovative operation strategies and performance outcomes of Malaysia manufacturing small and medium enterprises - Aghajari, Nezal (2015)
Innovation in operations is important for all small and medium enterprises (SMEs) especially in developing economies. This study examined the direct and indirect relations between strategic orientation, current and future innovative operation strategies, environmental uncertainties and the performance of Malaysia SMEs. Drawing on Market Based View (MBV), Resource Based View (RBV) and Dynamic Capabilities View (DCV) theories, a theoretical model consisting of firm’s strategic orientation, current innovative operation strategy, future innovative operation strategy, firm’s market performance, firm’s operational performance and environmental uncertainties was developed. Data were collected through a survey of 210 Malaysian manufacturing SMEs. A structural equation modeling (SEM) procedure was employed to test the hypotheses. The theoretical model was validated by empirical findings. This study found that strategic orientation positively influences a firm’s innovation in current and related future operations. Thus, a clear strategic orientation aligned with innovative operation strategy is a pre-requisite for SMEs. It was also confirmed that innovation of current and future operations could affect the operational and market performance of the firm. Furthermore, under conditions of uncertainty, firms which emphasize innovation in their operations are more likely to achieve better performance and could outperform their rivals. Drawing upon these findings, this study offers several important theoretical and managerial implications and opens up new areas for future research.